War and Peace in Sierra Leone - Richards, Paul (Tufts Archival Research Center, 2005)
Volume 25, Issue 2. Summer Richards challenges standard interpretations of the war in Sierra Leone, arguing that the international community has ignored the cause at the heart of the conflict: the failure to provide basic education to rural children.